A Proteomics Signature of Mild Hypospadias: A Pilot Study - Piñeyro-Ruiz, Coriness; Serrano, Horacio; Jorge, Inmaculada; Miranda-Valentin, Eric; Pérez-Brayfield, Marcos R.; Camafeita, Emilio; Mesa, Raquel; Vázquez, Jesús; Jorge, Juan Carlos (Frontiers in Pediatrics, 2020)
Background & Objective: Mild hypospadias is a birth congenital condition characterized by the relocation of the male urethral meatus from its typical anatomical position near the tip of the glans penis to a lower ventral position up to the brim of the glans corona, which can also be accompanied by foreskin ventral deficiency. For the most part, a limited number of cases have known etiology. We have followed a high-throughput proteomics approach to study the proteome in mild hypospadias patients. Methods: Foreskin samples from patients with mild hypospadias were collected during urethroplasty, while control samples were collected during elective circumcision (n = 5/group). A high-throughput, quantitative proteomics approach based on multiplexed peptide stable isotope labeling (SIL) and liquid chromatography-tandem mass spectrometry (LC-MS/MS) analysis was used to ascertain protein abundance changes in hypospadias patients when compared to control samples. Results: A total of 4,815 proteins were quantitated (2,522 with at least two unique peptides). One hundred and thirty-three proteins from patients with mild hypospadias showed significant abundance changes with respect to control samples, where 38 proteins were increased, and 95 proteins were decreased. Unbiased functional biological analysis revealed that both mitochondrial energy production and apoptotic signaling pathways were enriched in mild hypospadias. Conclusions: This first comprehensive proteomics characterization of mild hypospadias shows molecular changes associated with essential cellular processes related to energy production and apoptosis. Further evaluation of the proteome may expand the search of novel candidates in the etiology of mild hypospadias and could also lead to the identification of biomarkers for this congenital urogenital condition.